Climate change impact on food security: A review - Amelia Choya Tia Rosalia; Tri Mulyaningsih (Center for Science and Technology, IAIN Surakarta, 2022)
Countries all over the globe are facing climate change. Global warming is a real problem that occurs and affects food production. Â Precipitation and temperature rise are causes of the changes observed in this study. This study examines the relationship between food security level due to climate change. To provide further clarity, a systematic literature review (SLR) towards the impacts of climate change was conducted to identify the extent of its impacts on food security and to identify the extent of its impacts on the level of food security and research gaps. This systematic review identifies and analyzes documents on the impact of climate change on the level of food security in terms of the impact of climate change, the methods used to analyze climate change, and the available climate change adaptation policies. Following SLR guidelines, Google Scholar is the main database. This research can broaden our knowledge about the impacts of climate change and the role we can play in maintaining food security.